Answer:
it's 10
Step-by-step explanation:
i searched it up.
Top:
x / (x + 1) - 1 / x
= [x^2 - (x +1)] / x(x+1)
= (x^2 - x - 1 ) / x (x+1)
Bottom:
x / (x + 1) + 1 / x
= [x^2 + (x +1)] / x(x+1)
= (x^2 + x + 1 ) / x (x+1)
Now you have:
(x^2 - x - 1 ) / x (x+1)
----------------------------
(x^2 + x + 1 ) / x (x+1)
= (x^2 - x - 1 ) / x (x+1) * x (x+1) / (x^2 + x + 1 )
= (x^2 - x - 1 ) /(x^2 + x + 1 )
Answer:
x^2 - x - 1
---------------------
x^2 + x + 1
Answer:
60 degrees
Step-by-step explanation:
Answer:
Step-by-step explanation:
The function whose graph is given has y-intercept (0, 3), whereas the function f(x) has y intercept (0, 1). So it is the first that has the greater y intercept.